Polydatin Encapsulated Poly [Lactic-co-glycolic acid] Nanoformulation Counteract the 7,12-Dimethylbenz[a] Anthracene Mediated Experimental Carcinogenesis through the Inhibition of Cell Proliferation - Sankaran Vijayalakshmi; Arokia Vijaya Anand Mariadoss; Vinayagam Ramachandran; Vijayakumar Shalini; Balupillai Agilan; Casimeer C. Sangeetha; Periyasamy Balu; Venkata Subbaih Kotakadi; Venkatachalam Karthikkumar; David Ernest (MDPI AG, 2019)
In the present study, the authors have attempted to fabricate Polydatin encapsulated Poly [lactic-co-glycolic acid] (POL-PLGA-NPs) to counteract 7,12-dimethyl benzyl anthracene (DMBA) promoted buccal pouch carcinogenesis in experimental animals. The bio-formulated POL-PLGA-NPs were characterized by dynamic light scattering (DLS), Fourier transform infrared (FTIR) spectroscopy, X-ray powder diffraction (XRD) pattern analysis, and transmission electron microscope (TEM). In addition, the nano-chemopreventive potential of POL-PLGA-NPs was assessed by scrutinizing the neoplastic incidence and analyzing the status of lipid peroxidation, antioxidants, phase I, phase II detoxification status, and histopathological changes and in DMBA-treated animals. In golden Syrian hamsters, oral squamous cell carcinoma (OSCC) was generated by painting with 0.5% DMBA in liquid paraffin three times a week for 14 weeks. After 100% tumor formation was observed, high tumor volume, tumor burden, and altered levels of biochemical status were observed in the DMBA-painted hamsters. Intra-gastric administration of varying concentration of POL-PLGA-NPs (7.5, 15, and 30 mg/kg b.wt) to DMBA-treated hamsters assumedly prevents oncological incidences and restores the status of the biochemical markers. It also significantly enhances the apoptotic associated and inhibits the cancer cell proliferative markers expression (p53, Bax, Bcl-2, cleaved caspase 3, cyclin-D1). The present study reveals that POL-PLGA-NPs is a penitential candidate for nano-chemopreventive, anti-lipid peroxidative, and antioxidant potential, and also has a modulating effect on the phase I and Phase II detoxification system, which is associated with reduced cell proliferation and induced apoptosis in experimental oral carcinogenesis.